Changes in vaginal Ureaplasma and Lactobacillus due to antibiotic regimen for premature rupture of membranes - Haruna Kawaguchi; Yukiko Nakura; Ryo Yamamoto; Shusaku Hayashi; Makoto Takeuchi; Keisuke Ishii; Itaru Yanagihara (PLoS ONE, 2025)
Preterm premature rupture of membranes (PPROM) is associated with preterm delivery and neonatal complications. PPROM is often complicated by intra-amniotic inflammation and/or microbial invasion of the amniotic cavity with Ureaplasma or Mycoplasma. Various prophylactic antibiotic therapies have been proposed to prolong latency between PPROM and delivery, reduce the risk of clinical chorioamnionitis, and improve neonatal complications. However, information on the potential of azithromycin administration to reduce the microbial load of vaginal Ureaplasma and Mycoplasma remains lacking. This prospective cohort study included singleton pregnancies managed with prophylactic antibiotics for PPROM at less than 36 weeks of gestation. All patients received the standard antibiotic regimen for PPROM, which consisted of a single oral azithromycin and intravenous ampicillin every for 2 days followed by 5 days of oral amoxicillin. Vaginal swabs samples were collected when PPROM was confirmed and after the antibiotic regimen administration. The main outcome measures were to investigate the changes in vaginal Ureaplasma, Mycoplasma, and Lactobacillus spp. due to the antibiotic regimen. In addition, the association between the presence and changes in vaginal Ureaplasma and Mycoplasma, pregnancy outcomes, and neonatal complications were examined. Out of 82 eligible PPROM, 51 had positive vaginal Ureaplasma. Thirty-six patients (52.2%) completed the antibiotic regimen. Among those with positive vaginal Ureaplasma who completed the antibiotic regimen, 75% experienced an increase in vaginal Ureaplasma levels. For those who delivered before completing all antibiotic doses, 40% had increased vaginal Ureaplasma levels. Furthermore, the antibiotic regimen resulted in decreased Lactobacillus spp. in almost all cases. It was suggested that azithromycin and ampicillin may not be effective when targeting Ureaplasma or Mycoplasma. Since this study did not search for resistance genes, it cannot be determined that azithromycin resistance in Ureaplasma or Mycoplasma is responsible for the present results. In addition, vaginal Ureaplasma changes were not found to be associated with neonatal sepsis or bronchopulmonary dysplasia. Future studies are needed to revalidate current antibiotic therapy for PPROM.